The Contribution of the Consortium of Tanzania University and Research Libraries in Supporting Teaching and Research in Tanzanian Universities - Ntullo, Sayuni Harun; Jaiswal, Babita (University of Dar es Salaam Library Journal, 2024)
This study aimed to determine what the Consortium of Tanzania University and Research Libraries (COTUL) has done to improve teaching and research by Tanzanian universities. COTUL was founded in 2002 to link the then 76 member libraries electronically, thereby improving resource sharing and the collective nature of the institutions. A mixed-methods approach was employed to collect quantitative data through 154 distributed questionnaires and qualitative insights through in-depth interviews. A remarkable response rate of 77.9 percent has thus been ensured, suggesting robust engagement with the study. While the findings establish how COTUL has greatly enhanced scholarly access, it has had suboptimal utilization rates. It is reported that only 41 percent of the respondents utilise the sources provided to them every week. Barriers in training and marketing seem to be critical factors impeding fuller adoption. These notwithstanding, the benefits of COTUL's efforts to train library professionals and negotiate access to resources were well acknowledged to add more value to improving Tanzania's academic landscape. The end was with the recommendation that, if developed, their initiatives would better help in optimising resource utilisation towards the quality of teaching and research in Tanzania universities. This research recommended the need to have collaborative structures in library management, which call for proper sustained funding and strategic outreach for maximum impact by the consortium. Keywords: COTUL, Resource Sharing, Academic Libraries, Capacity-building, Information Technology https://dx.doi.org/10.4314/udslj.v19i2.5